Adoption Behaviour of Pigeonpea Growers in Allahabad District of Uttar Pradesh (Indian Journal of Extension Education, 2013)
Pigeonpea is most important pulse crop enterprise in U.P. Efforts are being made by extension functionaries to boost-up the production and productivity of the pigeon pea, even though, there exists the gap between the yield obtained at research farm and farmers’ field, it might be due to adoption gap. Keeping this in view an investigation was carried out in Karchhana block of Allahabad district during 2011-12 in order to determine the level of adoption of improved practices of pigeon pea production technology. The study inferred that majority of the respondents had medium level of adoption followed by high and low level of adoption. The variables like age, education, extension contact and mass media exposure were found to be positively and significantly corelated with the adoption behavior of the pigeon growers. There is a considerable scope for enhancing the production of the pigeon pea subject to the need based training imparted to the growers so that they could reap the benefits by adopting the improved package of practices.